2021
DOI: 10.1007/s00429-021-02286-9
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive approach to study the resting-state brain network related to creative potential

Abstract: Studies related to creativity generally investigate brain activity at rest using raw scores from only one creative task. However, considering all the factors that can impact the creative product, we believe that the creative potential of individuals must be evaluated to identify the associated resting-state brain networks. Moreover, studying the brain functional connectivity related to creativity processes should be considered in conjunction with cognitive functioning as both are composite phenomena. To test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
3
1
Order By: Relevance
“…In this study, we wanted to situate our intervention ahead of creative thinking, i.e., by acting on executive processes that will generate creative thinking. In a previous study (Deshayes et al, 2021), we showed that subjects with high creative potential show a positive correlation between working memory and creativity that we do not find in subjects with low creative potential. We believe that a focus on executive mechanisms that support creative thinking, some of them being involved in working memory, and on executive strategies could promote creative thinking use in a variety of contexts.…”
Section: Creativity and Problem Solvingcontrasting
confidence: 84%
“…In this study, we wanted to situate our intervention ahead of creative thinking, i.e., by acting on executive processes that will generate creative thinking. In a previous study (Deshayes et al, 2021), we showed that subjects with high creative potential show a positive correlation between working memory and creativity that we do not find in subjects with low creative potential. We believe that a focus on executive mechanisms that support creative thinking, some of them being involved in working memory, and on executive strategies could promote creative thinking use in a variety of contexts.…”
Section: Creativity and Problem Solvingcontrasting
confidence: 84%
“…For divergent thinking, the results showed that the analytic processing priming group performed lower fluency and flexibility scores than the control group, in line with Deshayes et al ( 2021 ). The divergent thinking task process allows people to generate as many responses (ideas, solutions) as possible under relatively weak constraints, and under this premise, lower levels of cognitive control may facilitate individuals to quickly “jump” from one idea to another ( Hommel et al 2011 ) and help allow more unfiltered information to enter the processing stage, thereby facilitating the generation of more divergent ideas ( Radel et al 2015 ).…”
Section: Discussionmentioning
confidence: 55%
“…A growing number of researchers have studied the relationship between analytic processing and creativity, but their findings vary widely ( Pennycook et al 2015 ). For example, some studies have shown a significant negative correlation between analytic processing and creativity ( Deshayes et al 2021 ), suggesting that analytic processing may be detrimental to a person’s ability to generate original ideas ( Nijstad et al 2010 ). However, other studies have shown that rational thinking can significantly and positively predict individual performance on verbal and figural creativity tasks ( Palmiero et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Creativity can be identified as a capacity that allows generating products that have originality and value ( Runco and Jaeger, 2012 ; Diedrich et al, 2015 ; Corazza, 2016 ; Romo, 2019 ). There is evidence indicating that this capacity has biological ( Sawyer, 2011 ; Penagos-Corzo, 2018 ; Deshayes et al, 2021 ), motivational ( de Jesus et al, 2013 ; Liu et al, 2016 ; Taylor and Kaufman, 2021 ), affective ( Baas et al, 2008 , 2011 ; Mielniczuk and Laguna, 2020 ) and cognitive components ( Benedek et al, 2014 ; Sampedro and Peña, 2019 ; Milicevic et al, 2020 ) that can enhance it. In addition to these components, some personality characteristics or traits have been associated with creativity practically since the contemporary beginning of its study ( Guilford, 1950 ; MacKinnon, 1963 ) and in influential later works ( Eysenck, 1993 , 1994 ; MacKinnon, 1975/2017 ).…”
Section: Introductionmentioning
confidence: 99%